2013
DOI: 10.1063/1.4819740
|View full text |Cite
|
Sign up to set email alerts
|

Clean transfer of graphene and its effect on contact resistance

Abstract: We demonstrate herein an effective method of forming a high-quality contact between metal and graphene on a wafer as large as 6 in. This gold-assisted transfer method producing no polymer residue on the graphene surface is introduced, and then the gold film is used directly as an electrode to form the transfer length method pattern for calculating the contact resistance. The graphene surface obtained using the gold-assisted transfer method is clean and uniform without residue or contamination, and its contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Nonetheless it has been reported that some PMMA residues still remain on the surface after thermal annealing, resulting in scattering and defects . In the absence of improved (i.e., low residue) graphene transfer techniques using PMMA or other polymers, the other option for wafer‐scale residue removal is wet‐chemical cleaning typically using organic solvents such as acetone, chloroform, etc . A major issue is that the presence and distribution of these polymer residues heavily depends on experimental conditions, the quality of graphene, etc., and therefore varies significantly from one process to another.…”
Section: Summary Of Test Results Of Electrical Characterization On Gfmentioning
confidence: 99%
“…Nonetheless it has been reported that some PMMA residues still remain on the surface after thermal annealing, resulting in scattering and defects . In the absence of improved (i.e., low residue) graphene transfer techniques using PMMA or other polymers, the other option for wafer‐scale residue removal is wet‐chemical cleaning typically using organic solvents such as acetone, chloroform, etc . A major issue is that the presence and distribution of these polymer residues heavily depends on experimental conditions, the quality of graphene, etc., and therefore varies significantly from one process to another.…”
Section: Summary Of Test Results Of Electrical Characterization On Gfmentioning
confidence: 99%
“…These contamination layers can confound the analysis of the graphene since a single nanometer of organic contamination will contain more carbon atoms than a single-layer of graphene. More significantly, however, surface contaminants can degrade the electrical performance of the graphene by acting as dopants and increasing contact resistance [8][9][10] . These effects are of particular concern for graphene grown by chemical vapor deposition (CVD) .…”
Section: Introductionmentioning
confidence: 99%
“…Typical transfer of graphene -grown by CVD on Cu or Ni substrates -onto a substrate of choice, involves some intermediate stages [1][2][3][4][5][6][7][8][9]. The graphene-deposited metal substrate is coated with a polymer, e.g., poly(methyl methacryslate) (PMMA) [1], or polydimethylsiloxane (PDMS) [2] in order to protect it through the following transfer stages.…”
Section: Introductionmentioning
confidence: 99%